Review of genus Conocephalus Thunberg, 1815 (Orthoptera: Tettigoniidae: Conocephalinae) with one new species from India - Farooqi, Mohd Kaleemullah; Usmani, Mohd Kamil (Zootaxa, 2018)
The present paper includes description of one new species Conocephalus (Anisoptera) rentzi sp. nov. and some known species of genus Conocephalus Thunberg, 1815 from India. Brief diagnosis of genus and subgenus with a key to species of subgenus Anisoptera and morphometric ranges of all the species are provided. The distributional map and illustrations of all the described and reported species with SEM photography of stridulatory files of C. (Anisoptera) maculatus & C. (Anisoptera) rentzi sp. nov. have also been included. All type specimens have been deposited for posterity in the Zoology Department, Aligarh Muslim University, India (ZDAMU).